Analisis Daya Saing Industri Tekstil dan Produk Tekstil (TPT) Indonesia Di Pasar ASEAN - Dwi Resti Pratiwi (Pusat Kajian Anggaran, 2020)
Indonesia is among the top 15 textile & apparel-producing countries in the world and therefore it is also one of the biggest textile producers in the ASEAN Market. This study examined the competitiveness of Indonesia TPT in the ASEAN market by using RCA methods and analyzed the determinant factors of its competitiveness by using the ordinary least square (OLS) regression method. The study period was from 2000-2019. Based on the calculation of the level of competitiveness by using RCA, showed that Indonesia's TPT industry has strong competitiveness (RCA>1) in the ASEAN market during 2000-2005. In the following years, however, its competitiveness decreased to below 1 point. So, Indonesia TPT did not have strong competitiveness during 2006-2019. Factors that affect of TPT Industry competitiveness of Indonesia are export price, REER, and investment. The government needs to be more serious to identify and solve the factors that inhibit the competitiveness of the textile industry.